The creative package: a working text for advertising copy and layout - Ernest, Sandra (Columbus: All Rights Reserved, 1979)
Los temas principales de este texto son: Research and analysis, creative Strategy, the creative idea, the right word, copy mechanics, graphic concept, layout and desing, lauout mechanics, multisensory impact, the complete package., entre otros
Incluye bibliografía
Keywords: Creatividad; Publicidad